Effect of combination of dye carotene and phycocyanin using daucus carota and spirulina sp. on optical sensor performance - Rahmadwati Rahmadwati; Luthfiyah Rachmawati; Panca Mudjirahardjo; Eka Maulana (Institute of Advanced Engineering and Science, 2020)
This research designed optical sensors using mercury lamp of 160W. These sensors provided voltage and current output. The design of optical sensors used the organic based material,i.e. dye carotene and phycocyanin. Fabrication of optical sensor in this research used spin coating deposition method. Based on the results of absorbance test, dye carotene had the largest absorption of light of 2.882 (a.u). Dye phycocyanin at length had the largest absorption of light of 2.787 (a.u). Combination between dye carotene and phycocyanin, for a 3: 1 (Carotene: Phycocyanin) ratio had a waveform like a dye carotene with a peak of 2.587 (au), whereas for 1: 3 had a waveform like phycocyanin with a peak of 2,279 (au). But, sample 1: 1 ratio had decrement the light absorbance rate with peaks of 1.183 (au). At the voltage testing result, combination of phycocyanin: carotene (1:3) had the best linearity. The response time of dye 3:1 (phycocyanin: carotene), 1:1, 1:3, phycocyanin, and carotene were 6.72 s, 2.469s, 1.171s, 2.66s and 7.01s respectively.